2022
DOI: 10.3390/s22218424
|View full text |Cite
|
Sign up to set email alerts
|

YOLOv5 with ConvMixer Prediction Heads for Precise Object Detection in Drone Imagery

Abstract: The potency of object detection techniques using Unmanned Aerial Vehicles (UAVs) is unprecedented due to their mobility. This potency has stimulated the use of UAVs with object detection functionality in numerous crucial real-life applications. Additionally, more efficient and accurate object detection techniques are being researched and developed for usage in UAV applications. However, object detection in UAVs presents challenges that are not common to general object detection. First, as UAVs fly at varying a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…The network structure of YOLOv5 is made up of Inputs, Backbone, Neck, and Prediction [20]. The input stage adopts techniques such as Mosaic data augmentation [21], adaptive anchor box calculation, and adaptive image scaling.…”
Section: The Network Architecture Of Yolov5mentioning
confidence: 99%
“…The network structure of YOLOv5 is made up of Inputs, Backbone, Neck, and Prediction [20]. The input stage adopts techniques such as Mosaic data augmentation [21], adaptive anchor box calculation, and adaptive image scaling.…”
Section: The Network Architecture Of Yolov5mentioning
confidence: 99%
“…Over the past decade, artificial intelligence has led to significant progress in the domain of computer vision, automating image and video analysis tasks. Among computer vision methods, Convolutional Neural Networks (CNNs) are particularly promising for future advances in automating wildlife monitoring [6,[12][13][14][15][16][17][18]. Corcoran et al [3] concluded that when implementing automatic detection, fixed-winged drones with RGB sensors were ideal for detecting larger animals in open terrain, whereas, for small, elusive animals in more complex habitats, multi-rotor systems with infrared (IR) or thermal infrared sensors are the better choice, especially when monitoring cryptic and nocturnal animals.…”
Section: Automatic Detection and Computer Visionmentioning
confidence: 99%
“…AP is the area under the precision-recall curve and provides a measure of the quality of the model’s predictions at different recall levels 38 …”
Section: Performance Metricsmentioning
confidence: 99%